Synthesis and characterization of ZnO–TiO2–chitosan–escin metallic nanocomposites: Evaluation of their antimicrobial and anticancer activities - Elderdery, Abozer Y.; Alhamidi, Abdulaziz H.; Elkhalifa, Ahmed M. E.; Althobiti, Maryam M.; Tebien, Entesar M. A.; Omer, Nawal Eltayeb; Hamza, Siddiqa M. A.; Alanazi, Fehaid; Alzahrani, Badr; Subbiah, Suresh Kumar; Pooi, Ling Mok (De Gruyter, 2022)
This work intended to formulate bio-nanocomposites of zinc oxide (ZnO), titanium oxide (TiO2), chitosan, and escin, characterize their physical properties, and evaluate their antimicrobial and anticancer properties. X-ray diffractometers (XRD) and scanning and transmission electron microscopes were applied to characterize the morphology and ultrastructure of chemically synthesized bio-nanocomposites. To investigate the functional groups of bio-nanocomposites, we used Perkin–Elmer spectrometers for Fourier transform infrared (FTIR) analysis and photoluminescence (PL) spectroscopy for PL spectrum analysis. Antimicrobial activities against bacterial and fungal strains were tested with agar well diffusion. Bio-nanocomposites were tested for anticancer effects on a MOLT4 blood cancer cell line using morphological analysis, methyl thiazole tetrazolium assay, apoptosis by acridine orange/ethidium bromide, and mitochondrial membrane potential (ΔΨm). In XRD, FTIR, and PL, the active compounds of ZnO–TiO2, chitosan, and escin peaks were observed. Our bio-nanocomposites demonstrated antimicrobial activity against bacterial and fungal pathogens. The bio-nanocomposite was cytotoxic to MOLT4 cells at an IC50 concentration of 33.4 µg·mL−1. Bio-nanocomposites caused cytotoxicity, changes in cell morphology, and mitochondrial membrane potential degradation, all of which resulted in apoptotic cell death. MOLT4 cells were found to be responsive to bio-nanocomposites based on ZnO–TiO2–chitosan–escin.